Modeling the Mechanical Integrity of Generic Solid Oxide Cell Stack Designs Exposed to Long‐term Operation. Issue 1 (19th December 2018) - Molla, T. T.; Kwok, K.; Frandsen, H. L.
Abstract: Thermal cycling and creep in metallic interconnects during operation of solid oxide cell (SOC) stacks could cause contact losses in the interface between the interconnect and cells. The magnitude of stress and its distribution within the SOC stack depends on the overall design of the stack and the operating conditions. In this study, stresses in different types of generic SOC stack designs caused by external loading and temperature variations through long‐term operation are investigated. The investigation includes stack designs with and without contact components combined with machined (cross‐shaped) or pressed (corrugated) interconnects. Two different generic temperature profiles in the stacks are considered. Special focus is given to stresses that can cause possible delamination of the interconnect from the cell that subsequently leads to loss of electrical contact. It is found that too rigid designs cause high stresses and creep in the interconnects, and so‐called stress reversal will cause delamination between interconnect and cell during shut‐down. Furthermore, the study also presents the effect of SOC stack design and/or thermal gradient on the magnitude of in‐plane stresses in the cells. Here it is found that it advantageous to cool the stack primarily with convection, as this causes a linear thermal profile and much lower stresses than if cooling is relying on conduction in the solids, as this causes a thermal gradient in several directions.